Comparison of Enoxaparin, Hirulog, and Heparin as Adjunctive Antithrombotic Therapy during Thrombolysis with rtPA in the Stenosed Canine Coronary Artery - Leadley, Robert J, Jr; Kasiewski, Charles J; Bostwick, Jeffrey S; Bentley, Ross; McVey, Matthew J; White, Francis J; Perrone, Mark H; Dunwiddie, Christopher T (Thrombosis and Haemostasis, 1997)
A canine model of electrolytic injury-induced coronary artery thrombosis and rtPA-induced thrombolysis was used to evaluate the relative antithrombotic efficacy of enoxaparin (a low molecular weight heparin), conventional therapy (heparin or heparin plus aspirin), and hirulog (a direct thrombin inhibitor), when used as adjunctive therapy during thrombolysis. After 60 min of clot aging, adjunctive therapy was begun at doses which elevated APTT approximately 2-fold over baseline. Fifteen minutes after the start of adjunctive therapy, recombinant tissue plasminogen activator (rtPA) was administered (100 μg/kg i.v. bolus + 20 μg/kg/min for 60 min). Adjunctive therapy continued for 1 h after termination of rtPA and blood flow was monitored for two additional hours. Enoxaparin (1 mg/kg i.v. bolus + 30 μg/kg/min, n = 10 for each treatment group) was the only adjunctive treatment that significantly increased the total minutes of flow (143 ± 25 min out of a possible 240 min, vs 54 ± 25 min for vehicle, p <0.05) and decreased thrombus mass (6.0 ± 1.3 mg vs 11.8 ± 3.2 mg for vehicle). Although hirulog (2 mg/kg i.v. bolus + 40 μg/kg/min) did not significantly increase the minutes of flow (120 ± 27 min, p <0.06) or decrease thrombus mass (8.7 ± 1.7 mg) compared to vehicle, these values were not significantly different than those measured in the enoxaparin group. However, the results with hirulog were achieved at the expense of a significantly greater increase in template bleeding time than that measured during enoxaparin treatment. Minutes of flow for heparin (50 U/kg i.v. bolus + 0.6 U/kg/min) and heparin plus aspirin (5 mg/kg i.v. bolus) were 69 ± 20 and 60 ± 23 min, respectively; thrombus masses were 8.2 ±1.3 and 7.3 ±1.0 mg, respectively. In summary, enoxaparin was more effective than conventional therapy in this model in terms of vessel patency and thrombus mass, and was as effective as hirulog, at least at a dose of hirulog that only modestly impaired hemostasis. Therefore, enoxaparin may prove to be a safe and effective alternative agent for adjunctive therapy during thrombolysis with rtPA.